Cancer cachexia: rationale for the MENAC (Multimodal—Exercise, Nutrition and Anti-inflammatory medication for Cachexia) trial. Issue 3 (9th February 2018) - Solheim, Tora S; Laird, Barry J A; Balstad, Trude R; Bye, Asta; Stene, Guro; Baracos, Vickie; Strasser, Florian; Griffiths, Gareth; Maddocks, Matthew; Fallon, Marie; Kaasa, Stein; Fearon, Kenneth
Abstract : Cancer cachexia is a multifactorial syndrome characterised by an ongoing loss of skeletal muscle mass that cannot be fully reversed by conventional nutritional support alone. Cachexia has a high prevalence in cancer and a major impact on patient physical function, morbidity and mortality. Despite the consequences of cachexia, there is no licensed treatment for cachexia and no accepted standard of care. It has been argued that the multifactorial genesis of cachexia lends itself to therapeutic targeting through a multimodal treatment. Following a successful phase II trial, a phase III randomised controlled trial of a multimodal cachexia intervention is under way. Termed the MENAC trial (Multimodal—Exercise, Nutrition and Anti-inflammatory medication for Cachexia), this intervention is based on evidence to date and consists of non-steroidal anti-inflammatory drugs and eicosapentaenoic acid to reduce inflammation, a physical exercise programme using resistance and aerobic training to increase anabolism, as well as dietary counselling and oral nutritional supplements to promote energy and protein balance. Herein we describe the development of this trial. Trial registration number: NCT02330926.